Algeria : 2009 Article IV Consultation; Staff Report; and Public Information Notice. (IMF Staff Country Reports; Country Report ;, 2010)
This report reviews the Article IV Consultation with Algeria on economic developments and policies. Algeria has enjoyed several years of strong economic performance driven by public spending, but continues to face important challenges. Nonhydrocarbon (NH) growth and job creation are largely sustained by public spending, highlighting the pressing need to accelerate structural reforms to diversify the economy, letting a competitive and outward-oriented private sector emerge. Executive Directors welcomed Algeria's strong economic performance in recent years, with solid NH growth and low inflation.